Cancer in printing workers in Denmark. Issue 11 (November 1995) - Lynge, E; Rix, B A; Villadsen, E; Andersen, I; Hink, M; Olsen, E; Møller, U L; Silfverberg, E
Abstract : OBJECTIVES–To study the cancer incidence in printing workers in Denmark. METHODS–The cohort of 15, 534 men and 3593 women working in the printing industry in 1970 were followed up for death, emigrations, and incident cancer cases until the end of 1987. Their cancer incidence was compared with that of all economically active people in Denmark. The smoking and drinking habits reported by members of the printing trade unions at a survey in 1972 were compared with habits reported by members of other trade unions. RESULTS–Lung, bladder, renal pelvis, and primary liver cancers were in excess among the printing workers. The excess risks of lung cancer among the factory workers in newspaper and magazine production, of bladder cancer in typographers in printing establishments, of renal pelvis cancer in typographers and lithographers, and of primary liver cancer among lithographers and bookbinders exceeded those expected based on the reported smoking and drinking habits. CONCLUSION–Our results indicate, in line with a previous study from Manchester, that work with rotary letterpress printing was associated with an increased risk of lung cancer. The inconsistent results from studies on bladder cancer in printing workers may point to a risk confined to a certain subgroup. The sixfold risk of primary liver cancer in Danish lithographers warrants studies in other countries.